A Research On Detecting The Place And Scope Of Underground Coal Fire Source In Coal Mine With Radon - Deli Hu; Xiangze Shu; Hongfu Liu; Cai Wang (Society for Mining, Metallurgy & Exploration, 1991)
To detect the place and range of fire is one of the key technologies in the extinction of coal mine underground fire. A fire-prevention and extinction research team of Shanxi Mining College have successfully carried out a program detecting the place of fire with radon. In the past four years the authers have done the detecting work in several mines in Shanxi Province, such as Gujao, Xuangang Louan and Ningwu. The place and scope and the trend of underground fire of coal mine can be now exactly estimated. The data and information from detecting provide a reliable basis for drawing up the scheme to extinguish underground fire and extract mineral coal securely. The principle and method of fire detecting based on radon on surface, the data processing and analysis are discussed in this paper.